Upaya Strategis Kepala Sekolah dalam Mewujudkan Pendidikan Ideal di MA Al-Ishlah Bilapora Barat Ganding Sumenep Madura - Misnawi, Misnawi; Ubaidillah, Muhammad Farah; Zainudin, Zainudin (Empiricism Journal, 2022)
A quality education is so far becoming a main target and objective in every educational practice.  It has very close correlation with principals policies in carrying out an institutional management. This research tries to analyse and explain some strategic efforts of the principal of Al-Ishlah Islamic Senior high school (MA) Bilapora Ganding Sumenep in realizing an ideal education and identify also the hinderances in implementing it. This is a field research using a qualitative approach. There are three informen in this research i.e. the principal of MA Al-Ishlah as the main informan and two additional ones namely a vice principal and a teacher by using purposive method. The research is accomplished through several procedures i.e. collecting data by interview technique, analyzing data, validating data and taking conclusion. Then, Every data collected is analysed by using analytical-descriptive method. Based on the result of study or research, we know that there are some strategic principals efforts in realizing an ideal education through several ways, namely: developing relevant curriculums, preparing professional teachers, realizing a professional service standard for students, building an intensive relation with surrounding community, and creating a representative, enjoyable, and character school environment. In implementing those all, the principal faces several kinds of obstacle factors, including: limited land extent for broadening classroom, amount of nonlinear teacher, limited availability of school facilities, and also limited and minimal funding resources. Those are the most urgent factors which need the alternative solutions soon. So that the principals efforts above can be achieved well.